PENGARUH-LIKUIDITAS,-LEVERAGE,-DAN-SIZE-PERUSAHAAN-TERHADAP NILAI-PERUSAHAAN-DENGAN-PROFITABILITAS-SEBAGAI-VARIABEL MEDIASI: (Studi-Pada-Perusahaan-Sub-Sektor-Food and Beverages-yang-Terdaftar-di-Bursa-Efek Indonesia-(BEI)-Periode-2020-2022) - Yulsa Aldi Pratama; Sigit Santoso (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
The purpose of the study is to analyze the relationship between liquidity, leverage, and company value on the value of a company by using profitability for mediating variables in food & beverages subsector companies listed on the Indonesia Stock Exchange (IDX) in the 2020-2022 period. Quantitative methods are used in this study by taking secondary data obtained from the company's annual report. The sampling technique in this study was purposive sampling method and obtained a sample of 17 companies and 3 years of observation and smartPLS 4 as a tool for analyzing data. This study found that Leverage, Company Size, and Profitability have a significant effect on Firm Value. In addition, there are no variables that have a significant effect on Profitability and Profitability is not able to mediate the relationship between Liquidity, Leverage, and Company Size on Company Value in food & beverage sub-sector companies listed on the Indonesia Stock Exchange in the period 2020-2022.